Experimental comparison of the structural, magnetic, electronic, and optical properties of ferromagnetic and paramagnetic polycrystalline Zn1-xCoxO (x=0,0.05,0.1) - Deka, Sasanka; Pasricha, Renu; Joy, Pattayil Alias (Physical Review B, 2006)
Ferromagnetism at room temperature is observed in one case whereas paramagnetism down to 12 K is observed in the second case when polycrystalline Zn1-xCoxO is synthesized under almost identical conditions. Identical x-ray diffraction, optical absorption, and x-ray photoelectron spectroscopy results indicate the incorporation of Co2+ ions in the ZnO lattice in both cases. However, electron diffraction studies show the presence of Co metal impurities in the ferromagnetic samples, indicating that pure Co doped ZnO is not likely to be ferromagnetic.